PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT, PENGUNGKAPAN INTELLECTUAL CAPITAL, DAN STRUKTUR PENGELOLAAN PADA NILAI PERUSAHAAN - Candra, Ana Dwiyanti; Wiratmaja, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.06.TAHUN 2020DO - 10.24843/EEB.2020.v09.i06.p05, 2020)
Firm value considered by investor to make investment decision. Higher firm value influenced the investor’s confidence to invest on a firm. Based on the phenomenon and associated theory, firm value influenced by ERMD, ICD, and management structure. This research aims to find out empirical evidence on the ERMD, ICD, and management structure (proxied with independent commissioner proportion). This research conducted at bank firms listed on Indonesia Stock Exchange in 2016-2018. Purposive sampling method used in the sample selection, obtaining 31 banks as the sample with total 93 data during 3 years. There are 7 data outliers excluded from the analysis in order to obtain as many as 86 data. Using MRA, obtained results that only the ERMD variable that positively influenced firm value while the other two independent variables has no effect on firm value.